Merit2U: an IoT-based merit point management system for university students' hostel application - Ishak, Iskandar; Abdul Rahman, Nur Shahirah; Hamdan, Hazlina; Sidi, Fatimah (IEEE, 2017)
Merit2U is a web-based system to manage merit points for students' college application. This system provides better merit point management where the points are calculated automatically and electronically using web-based application.